RHEUMATOID ARTHRITIS: ETIOLOGY, SYMPTOMS, DIAGNOSIS, TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article discusses the etiology, pathogenesis, clinical manifestations, diagnostic approaches and modern treatment strategies of rheumatoid arthritis based on the most recent data.